LAND‐USE SYSTEM AND SPATIAL PLANNING IN FRANCE - Dorosh, O. S.; Loyik, H. K. (Землеустрій, кадастр і моніторинг земель, 2013)
Experience of land management and land administration, spatial   planning in France is analyzed.